Evolution of cafeteria systems – past-present and future - Beke, Jenő; László, Gyula; Óhegyi, Katalin; Poór, József (Studia Mundi – Economica, 2014)
The authors first review the most important features of the cafeteria system (goals, typical ‘stakeholders’ and strategic HR issues). Then they examine the evolution of the system of flexible benefits since 1996, when the first such systems appeared in Hungary. Authors also analyze how the main drivers caused the changes, and how the key players of the cafeteria systems adapted themselves to these movements. The reader can also find insight into the major changes for 2012 and the potential impact of these changes on benefit policies of Hungarian firms. They also touch upon the findings of empirical surveys that the cafeteria systems are significantly influenced mainly by the size of organizations and to a lesser extent by form of ownership.
Keywords: fringe benefits; flexible remuneration; cafeteria benefits; Hungary